Cross-language information retrieval: experiments based on CLEF 2000 corpora - Savoy, Jacques (My University, 2003)
Search engines play an essential role in the usability of Internet-based information systems and without them the Web would be much less accessible, and at the very least would develop at a much slower rate. Given that non-English users now tend to make up the majority in this environment, our main objective is to analyze and evaluate the retrieval effectiveness of various indexing and search strategies based on test-collections written in four different languages: English, French, German, and Italian. Our second objective is to describe and evaluate various approaches that might be implemented in order to effectively access document collections written in another language. As a third objective, we will explore the underlying problems involved in searching document collections written in the four different languages, and we will suggest and evaluate different database merging strategies capable of providing the user with a single unique result list. (C) 2002 Published by Elsevier Science Ltd.
Keywords: cross-language information retrieval; bilingual information retrieval; French; German Italian languages; database merging strategies; evaluation; TEXT RETRIEVAL; SEARCH TERMS; ALGORITHM; SELECTION; QUERIES; LIFE; WEB